Insecticidal Effect of Adathoda vasica (Leaf) and Trigonella foenum – Graecum (Seed) Extracts against Mealy Bugs (Maconellicoccus hirsutus) On Hibiscus Rosa sinensis Plant - Mohamed, Kalitha Parveen Peer; Sundaralingam, M; Sukumaran, Athira; S, Christobher (Asian Journal of Biological and Life Sciences)
Biopesticides are natural plant products which are environmentally safe, less hazardous, economic and easily available. Mealy bugs are white to pink in colour and measure 3–4 mm in length. In case of M. hirsutus, eggs as well as crawlers are pink in colour. Two plant species; were tested as an alternative insecticidal. A. vasica leaves and T. foenum-graecum seeds. The insecticidal results are also comparable with earlier reports, the data on the mortality of the mealy bug nymph’s show that all the treatments were highly significant over control. The experiments were conducted in a petriplate at 25-26°C and under long daylight Analyses of data were performed using statistical program SPSS. Toxicity of two different types of botanical extracts tested against hibiscus mealy bug adults was determined by calculating median lethal concentration (LC50) values. The 24 hr LC50 values for the seed extract of Trigonella foenum-graecum is 28.18ppm and 24.54ppm respectively for ethanol against Maconellicoccus hirsutus. The 24 hr LC50 values for the leaf extract of Adathoda vasica is 25.70ppm and 39.81ppm respectively for ethanol Maconellicoccus hirsutus. The extracts were relatively more toxic to the mealy bug Maconellicoccus hirsutus. The leaf extract of these two plants therefore could be potential source of herbal insecticide for mealy bug population control and could be used in integrated vector management.
Keywords: Adathoda vasica; Lethal concentration; Maconellicoccus hirsutus; Trigonella foenum-graecum; Vector management